""Turn‐On" Sensing Behaviour of an In Situ Generated Fluorescein‐Based Probe and Its Preferential Selectivity of Sodium Hypochlorite over tert‐Butyl Hydroperoxide in Lung Adenocarcinoma Cells". Issue 4 (24th January 2020) - Sandhu, Navjot; Saproo, Sheetanshu; Naidu, Srivatsava; Singh, Atul P.; Kumar, Kamlesh; Singh, Ashish P.; Yadav, Rajesh K.
Abstract: Reactive Oxygen species (ROS) are well known for their oxidizing behaviour but it differs in fluorescein derivatives chemistry. With t ‐BuOOH, the probe F shows its unique turn‐off sensing (A), while with NaOCl probe shows turn‐on sensing property (B). In this study, it was observed that in situ generated species formed by the reaction of probe (F) with t ‐BuOOH is a unique molecule, having high turn‐on behaviour in presence of sodium hypochlorite (≈500 times). Further, fluorescence microscopy imaging using adenocarcinoma cells, A549 cells revealed that in‐situ generated molecule, could be used as an efficient fluorescent probe for detecting NaOCl in living cells. Abstract : With fluorescein‐based probe F, t ‐BuOOH shows its unprecedented reducing behavior with "turn‐off" sensing, while in‐situ generated probe A by the reaction of t ‐BuOOH with Probe F, shows "turn‐on" sensing property with NaOCl.